Controlling nasal hemorrhage - Ashjai Sh (Iran University of Medical Sciences, 1989)
Talented individuals, who are bleeding from the nose, usually do not go to the doctor, except in case of sever and unusual bleeding. Because traditional method of treatment is not effective in nasopharanx bleeding, so Malcolm Harvey explain Brighton epistaxis balloon as a new method  for controlling nasopharanx bleeding through the paper. Epistaxia usually happen in the anterior part of the nasal septum which is full of capillaries. But in some cases bleeding happen in an area near the back of the throat. So the use of electrical burning and silver Nitrat solution is not possible. Also due to lack of access to bleeding point, traditional packing is not possible.